MODEL GERAKAN REKLAIMING TANAH DALAM PERSPEKTIF MASYARAKAT ADAT KASUS DI WILAYAH KABUPATEN KOTAWARINGIN TIMUR - Joni Rusmanto; Ester Sonia Ulfaritha (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
Tenure conflicts between indigenous communities and plantation companies are based on differences in the legality of claims. The community as a subsystem of traditional farmers underlies the claim of management rights based on traditional knowledge. On the other hand, plantation companies based the legality of claims based on agrarian law that is normative positivistic with a capitalistic economic orientation. In Henri Lefebvre's perspective, in fact there is no completely "ideal" space because space itself is spatially in modern capitalist society as an arena of battle that will never be completely contested. All interested parties will continue to try to find ways to dominate the use or utilization of a space and reproduce all knowledge to maintain their hegemony over the use of that space. In that context, social movements can be understood as community efforts in producing social space.